KEBIJAKAN HUKUM PIDANA TERKAIT PEMIDANAAN TERHADAP PEJABAT NEGARA DI BIDANG PERTAHANAN YANG MELAKUKAN KEJAHATAN TERHADAP KEMANUSIAAN SEBAGAI BENTUK PELANGGARAN HAK ASASI MANUSIA BERAT - Naufal Nata Prawira; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Regulations regarding serious human rights, especially regarding state officials in thedefense sector, are regulated in Law Number 26 of 2000 concerning Human Rights Courts,however, in this regulation there is a problem where there is no distinction between theimposition of criminal sanctions between state officials and the public. in general. This canbe seen in article 42 paragraph (3) which regulates the punishment of state officials in thesecurity sector who commit crimes against humanity. This article refers to article 37 as thebasis for the punishment of state officials.This type of research can be classified as normative research which examines legalprinciples, namely the principle of criminal responsibility. This research uses secondary databy elaborating on primary, secondary and tertiary legal materials that are relevant to theresearch topic.Based on the results of the research, it can be concluded that firstly, the absence ofdifferences in the imposition of criminal sanctions between state officials in the defensesector who commit crimes against humanity and ordinary people makes the currentregulations weak. This can be seen in Article 42 paragraphs 1 and 3 of Law Number 26 of2000 concerning Human Rights Courts which have been the source of law for resolvingserious human rights cases and in Article 599 of Law Number 1 of 2023 concerning theCriminal Code which has many problems in the regulations. This means reducing theminimum criminal sentence for someone who commits crimes against humanity. Secondly, informing regulations it is actually necessary to consider philosophical, sociological andjuridical factors. In the case of Brigadier General TNI M. Noer Muis in the East Timor case,he was acquitted of all charges against him and Infantry Major Isak Sattu in the Panai casewas deemed not guilty of the actions he committed, the results of this verdict show that justicehas not been implemented in society. Therefore, it is necessary to reform the criminal law inincreasing punishment for state officials in the defense sector who commit crimes againsthumanity in Indonesia.Keywords: Criminal Law Policy, Sentencing, State Officials, Crimes Against Humanity